Brain-derived extracellular vesicles mediated coagulopathy, inflammation and apoptosis after sepsis. Issue 207 (November 2021) - Lin, Huaying; Chen, Hongguang; Qi, Bo; Jiang, Yi; Lian, Naqi; Zhuang, Xiaoli; Yu, Yonghao
Abstract: Introduction: The activation of coagulation, inflammation and other pathways is the basic response of the host to infection in sepsis, but this response also causes damage to the host. Brain-derived extracellular vesicles (BDEVs) have been reported to cause a hypercoagulable state that can rapidly develop into consumptive coagulopathy, which is consistent with the pathophysiological process of sepsis-induced coagulopathy. However, the role of BDEVs in sepsis-induced coagulopathy remains unclear. Materials and methods: Male Sprague-Dawley (SD) rats were used for sepsis modeling using cecal ligation puncture (CLP). Flow cytometry was used to measure the levels of circulating BDEVs. Enzyme-linked immunosorbent assay (ELISA) was used to measure the serum levels of plasminogen activator inhibitor type 1 (PAI-1), thrombin-antithrombin (TAT), D-dimer, fibrinogen(Fib), tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β and IL-6. Nanoparticle tracking analysis (NTA) and Transmission electron microscopy (TEM) were used to identify BDEVs. Western blot (WB) was used to determine the expression of glial fibrillary acidic protein (GFAP), neuron-specific enolase (NSE), bax, bcl-2 and cleaved caspase-3. Hematoxylin-eosin (HE) and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining were performed to detect tissue injury. Survival was monitored over the course of 168 h. Results: We found that a large number of BDEVs were released into the circulating blood in septic rats. Moreover, we observed that BDEVs injection activated the systemic coagulation reaction and induced lung, liver and kidney inflammation and apoptosis(P < .05). Compared with BDEVs from sham-operated rats, BDEVs from septic rats exacerbated this process(P < .05). Conclusions: This finding suggests that inhibiting BDEVs may yield therapeutic benefits in the treatment of sepsis-induced coagulopathy. Highlights: Brain-derived extracellular vesicles were released into blood in septic rats. Brain-derived extracellular vesicles induced coagulopathy and tissue damage. Brain-derived microvesicles from septic rats aggravated coagulopathy and organ injury.